Antiplatelet therapy in patients with conservatively managed spontaneous coronary artery dissection from the multicentre DISCO registry. (2nd August 2021) - Cerrato, Enrico; Giacobbe, Federico; Quadri, Giorgio; Macaya, Fernando; Bianco, Matteo; Mori, Ricardo; Biolè, Carlo Alberto; Boi, Alberto; Bettari, Luca; Rolfo, Cristina; Ferrari, Fabio; Annibali, Gianmarco; et al.
Abstract: Aims: The role of antiplatelet therapy in patients with spontaneous coronary artery dissection (SCAD) undergoing initial conservative management is still a matter of debate, with theoretical arguments in favour and against its use. The aims of this article are to assess the use of antiplatelet drugs in medically treated SCAD patients and to investigate the relationship between single (SAPT) and dual (DAPT) antiplatelet regimens and 1-year patient outcomes. Methods and results: We investigated the 1-year outcome of patients with SCAD managed with initial conservative treatment included in the DIssezioni Spontanee COronariche (DISCO) multicentre international registry. Patients were divided into two groups according to SAPT or DAPT prescription. Primary endpoint was 12-month incidence of major adverse cardiovascular events (MACE) defined as the composite of all-cause death, non-fatal myocardial infarction (MI), and any unplanned percutaneous coronary intervention (PCI). Out of 314 patients included in the DISCO registry, we investigated 199 patients in whom SCAD was managed conservatively. Most patients were female (89%), presented with acute coronary syndrome (92%) and mean age was 52.3 ± 9.3 years. Sixty-seven (33.7%) were given SAPT whereas 132 (66.3%) with DAPT. Aspirin plus either clopidogrel or ticagrelor were prescribed in 62.9% and 36.4% of DAPT patients, respectively. Overall, a 14.6% MACE rate was observed at 12 months of follow-up. Patients treated with DAPT had a significantly higher MACE rate than those with SAPT [18.9% vs. 6.0% hazard ratios (HR) 2.62; 95% confidence intervals (CI) 1.22–5.61; P = 0.013], driven by an early excess of non-fatal MI or unplanned PCI. At multiple regression analysis, type 2a SCAD (OR: 3.69; 95% CI 1.41–9.61; P = 0.007) and DAPT regimen (OR: 4.54; 95% CI 1.31–14.28; P = 0.016) resulted independently associated with a higher risk of 12-month MACE. Conclusions: In this European registry, most patients with SCAD undergoing initial conservative management received DAPT. Yet, at 1-year follow-up, DAPT, as compared with SAPT, was independently associated with a higher rate of adverse cardiovascular events (ClinicalTrial.gov id: NCT04415762). Graphical abstract: